Reflector Localization of Breast Lesions and Parameters Associated with Positive Surgical Margins in Women Undergoing Breast Conservation Surgery. Issue 5 (7th July 2020) - Kuzmiak, Cherie M; Kim, Suk Jung; Lee, Sheila S; Jordan, Sheryl G; Gallagher, Kristalyn K; Ollila, David W; Zeng, Donglin
Abstract: Objective: To evaluate our experience with reflector localization of breast lesions and parameters influencing surgical margins in patients with a malignant diagnosis. Methods: A retrospective institution review board–approved review of our institutional database was performed for breast lesions preoperatively localized from September 1, 2016, through December 31, 2017. Wire localizations were excluded. From electronic medical records and imaging, the following data was recorded: breast density, lesion type and size, reflector placement modality and number placed, reflector distance from lesion and skin, excision of lesion and reflector, tissue volume, margin status, and final pathology. Statistical analysis was performed with a Fisher's exact test, Mann-Whitney test, and logistic regression. P < 0.05 was significant. Results: A total of 111 reflectors were deployed in the breasts of 103 women with 109 breast lesions. Ninety (81.1%) reflectors were placed under mammographic guidance and 21 (18.9%) under US. The lesions consisted of 68 (62.4%) masses, 17 (15.6%) calcifications, 2 (1.8%) architectural distortions, and 22 (20.2%) biopsy markers. Fourteen (21.2%) of 66 cases with a preoperative malignant diagnosis had a positive surgical margin. Final pathology, including 6 lesions upgraded to malignancy on excision, demonstrated 72 (66.0%) malignant, 22 (20.2%) high-risk, and 15 (13.8%) benign lesions. Univariate and multivariate analysis revealed no statistically significant parameters (lesion type or size, placement modality, reflector distance to skin or lesion, specimen radiography or pathology) were associated with a positive surgical margin. Conclusion: Reflector localization is an alternative to wire localization of breast lesions. There were no lesion-specific or technical parameters affecting positive surgical margins. Graphical Abstract: